Chitosan-alginate microcapsules: A strategy for improving stability and antibacterial potential of bovine Lactoferrin - Cots, Agustina; Camacho, Nahuel Matías; Palma, Santiago Daniel; Alustiza, Fabrisio Eduardo; Pedraza, María del Luján; Bonino, Facundo; Carreño, Joel; Flores Bracamonte, Carolina; Acevedo, Diego; Bozzo, Andrea; Bellingeri, Romina (Elsevier, 2026)
Lactoferrin, a multifunctional glycoprotein with significant biological properties, presents significant potential for the prevention and treatment of infectious diseases. However, the effectiveness of oral Lactoferrin is limited by its susceptibility to degradation in harsh stomach conditions, reducing its bioavailability and therapeutic efficacy. To address this challenge, this study employs Chitosan/Alginate microparticles to enhance Lactoferrin stability and antibacterial activity. Microparticles were synthesized through external ionic gelation and thoroughly characterized. Chitosan/Alginate microparticles were significantly smaller than Alginate microparticles, with a high loading efficiency of 93.65 %. Fourier transform infrared (FT-IR) spectroscopy confirmed the successful incorporation of Lactoferrin. Release studies demonstrated minimal Lactoferrin release in simulated gastric fluid, while a controlled release was observed in simulated intestinal fluid. Notably encapsulated Lactoferrin retained its structural integrity after exposure to simulated gastrointestinal conditions. Antibacterial assay against Escherichia coli showed that Chitosan/Alginate microcapsules maintain Lactoferrin antibacterial activity after its passage through simulated gastrointestinal conditions. Furthermore, FT-IR spectroscopy and zeta-potential analysis provided novel insights into the mechanism of Lactoferrin's interaction with bacterial LPS, highlighting its ability to destabilize bacterial membrane of this Escherichia coli strain. These findings underscore the Chitosan/Alginate system as a promising strategy for enhancing the therapeutic potential of Lactoferrin.